2018
DOI: 10.1021/acs.jafc.7b06130
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations on the Stability and Release Properties of β-ionone Loaded Thermosensitive Liposomes (TSLs)

Abstract: Liposomes with phase transition temperatures, T, near pathogenic site temperature are potential chemoprophylactic delivery vehicles. We prepared and characterized the thermal properties of liposomes composed of 1,2-dipalmitoyl- sn-glycero-3-phosphocholine (DPPC) and hydrogenated soy phosphatidylcholine (HSPC) incorporating β-ionone with T at 42 °C. Liposomes with β-ionone/lipid ratio (w/w) of 1:20 and 1:8 had the necessary stability and released most of the β-ionone. The molecular architecture surrounding T wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
(100 reference statements)
0
10
0
Order By: Relevance
“…This research focused on the development of liposomes as delivery systems because of their potential benefits for food and beverage applications. , CSO and βC were examined because of their potential health benefits . Previously, liposomes have been shown to be suitable for encapsulation of either CSO or βC individually. , These studies showed that their stability and bioavailability could be enhanced using liposomal formulations.…”
Section: Discussionmentioning
confidence: 99%
“…This research focused on the development of liposomes as delivery systems because of their potential benefits for food and beverage applications. , CSO and βC were examined because of their potential health benefits . Previously, liposomes have been shown to be suitable for encapsulation of either CSO or βC individually. , These studies showed that their stability and bioavailability could be enhanced using liposomal formulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, a better encapsulation efficiency (34.6%) of nisin Z in hydrogenated phospholipid liposomes was obtained, compared with liposomes contained a high percentage of unsaturated phospholipids (Laridi, Kheadr, Benech, Vuillemard, Lacroix, & Fliss, 2003). Chen et al confirmed that a greater HSPC content leads to the higher phase transition temperature of liposomes, due to the longer alkyl chain and stronger chain-chain van der Waals interactions (Chen, Liang, Wang, Yokoyama, Chen, & Zhong, 2018). It is worth noting that the cost of hydrogenated phospholipids is much higher than that of unsaturated ones, which make it unrealistic to prepare liposomes using hydrogenated phospholipids alone in food processing.…”
Section: Introductionmentioning
confidence: 99%
“…β-Ionone is a natural product which is prevalent in fruits, flowers, and vegetables. 20 To further demonstrate the synthetic practicability, late-stage diversification of β-ionone derivative 1an was carried out, delivering the corresponding product 3an in 39% yield (Scheme 6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%